Exploring Viral Interference Using Peptides: Molecular Determinants of HIV-1 Inhibition by a Peptide Derived from Human Pegivirus-1 Envelope Protein E2 - Hoffmann, Rebecca; Ruegamer, Tamara; Schaubaecher, Johanna; Rohrhofer, Anette; Kirmeß, Peter; Fiebig, Karen; Schmidt, Barbara; Eichler, Jutta (ChemMedChem, 2021)
Co-infection with the human pegivirus 1 (HPgV-1) often has a beneficial effect on disease progression in HIV-1-infected individuals. Several HPgV-1 proteins and peptides, including a 20-mer peptide (P6-2) derived from the N-terminal region of the HPgV-1 surface protein E2, have been associated with this phenomenon, which is referred to as viral interference. We identified the cysteine residues, the hydrophobic core tetrapeptide, as well as the C-terminal negative charge as key factors for the HIV-1 inhibitory activity of P6-2. Analysis of mutations in P6-2-resistant HIV-1 indicated a binding site for the peptide in the HIV-1 envelope glycoprotein gp120. In fact, P6-2 was shown to bind to soluble gp120, as well as to a peptide presenting the gp120 V3 loop. Furthermore, the HIV-1 inhibitory activity of P6-2 could be revoked by the V3 loop peptide, thus indicating a molecular mechanism that involves interaction of P6-2 with the gp120 V3 loop.
CRIS-Team WoS Importer:2021-02-19